Epithelioma Caniculatum - Chatterjee Tapas Kumar; Sadhu Sisir Kumar (Wolters Kluwer Medknow Publications, 1997)
A 57 year old man had a cauliflower growth over his right sole for 2 years. Biopsy revealed pseudoepitheliomatous changes with no evidence of malignancy. Chemical cautery with trichloroacetic acid and salicylic acid was un satisfactory